Integration of Strategic Management and SIJAMIN Application in Improving the Quality of Higher Education - Sayni Nasrah; Syamsul Arif; Eka Daryanto; Sri Milfayetty; Wanapri Pangaribuan (Jurnal Paedagogy, 2024)
This research aims to analyze the integration of strategic management using SIJAMIN to conduct internal quality audits (IQA) at Universitas Malikussaleh in Lhokseumawe. This research used a qualitative approach with a descriptive method. Data collection techniques through observation, interviews with the Head, Secretary, Head of the Audit Center, and Accreditation Supervisor of the Learning Development and Quality Assurance Institute (LP3M), and documentary analysis to examine and evaluate the 2020-2024 Strategic Plan. This data analysis technique used interactive model analysis. Research validity was ensured through data triangulation, utilizing multiple data sources to guarantee the accuracy and reliability of findings. The results indicated that strategic management was implemented using the SWOT analysis model. The University's strategic plan for 2020-2024 focused on the policy of independent learning as a guideline for human resource development, considering global trends such as technological advancements. SIJAMIN is one of UNIMAL's missions in the technology field and is used to implement the Internal Quality Assurance System (SPMI), held annually in the form of internal quality audits (IQA). The application of SIJAMIN in the 6th IQA cycle showed that it could facilitate real-time data-driven decision-making, improve operational efficiency, and strengthen coordination among units. Additionally, there was progress in achieving strategic goals and enhancing the quality of teaching, research, and community service, with the expectation of achieving excellent accreditation. In conclusion, integrating strategic management and implementing SIJAMIN is a practical strategic step in improving the quality of higher education, particularly at Universitas Malikussaleh.